Users' Perspectives on Ethical Issues Related to Playing Location-Based Augmented Reality Games: A Case Study of Pokémon GO. Issue 2 (20th January 2023) - Lee, Jin Ha; Yip, Jason; Moore, Adam; Cho, Yeonhee; de Jong, Zale; Kobashigawa, Ryan; Sanchez, Alexander Escalera
ABSTRACT: Location-based augmented reality games are becoming increasingly popular, which causes a variety of tensions among players as well as between players and non-players. Subsequently, numerous ethical issues and challenges in designing and playing these games emerged. We conducted an online survey and analyzed 2, 023 responses to better understand users' participation in various game actions in location-based augmented reality games, and their perspectives on how ethical the actions are and for what reasons. We provide descriptive statistics showing people's participation in these actions and analyze users' expressed reasons as to why they think these actions are ethical or not. We use the theoretical lens of three ethical traditions–consequentialism, deontology, and virtue ethics–in our analysis, showing the dominance of consequentialism and deontology in people's ethical judgment related to playing the game, and discuss implications and future consideration for game design.